2008
DOI: 10.1108/17471110810892839
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social and environmental reporting: a survey of disclosure practices in Egypt

Abstract: Purpose -The purpose of this study is to survey the corporate social and environmental reporting (CSR) practices of Egyptian corporate entities. It aims at contributing to the body of knowledge on the CSR disclosure phenomenon in developing/transitional economies.Design/methodology/approach -A 34-item disclosure index covering environmental, energy, human resources, customer and community involvement issues was used to rank corporations.Findings -A review of a random sample of 60 annual reports for the 2002 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 39 publications
11
135
1
5
Order By: Relevance
“…In addition, most disclosed information related to employee issues. In other study conducted in Egyptian context, Rizk et al (2008) studied corporate social and environmental reporting practices of Egyptian corporate entities. Findings of the study indicate a significant variation regarding social and environmental disclosure practices in 60 companies operating in industrial segments.…”
Section: Petroleum Industry In Middle East and North Africa (Mena)mentioning
confidence: 99%
“…In addition, most disclosed information related to employee issues. In other study conducted in Egyptian context, Rizk et al (2008) studied corporate social and environmental reporting practices of Egyptian corporate entities. Findings of the study indicate a significant variation regarding social and environmental disclosure practices in 60 companies operating in industrial segments.…”
Section: Petroleum Industry In Middle East and North Africa (Mena)mentioning
confidence: 99%
“…He found that there are significant differences among the various industry groupings with respect to the amounts, methods and locations. This finding is confirmed by Ahmad et al (2003), Ayadi (2004) in France, Rizk et al (2008) in Egypt, in Jordan, Echave and Bhati (2010) in Spain, Papaspyropoulos et al (2010) in Greece, Uwalomwa andUadiale (2011) in Nigeria, Bayoud et al (2012) in Libya; Wang et al (2012) in Taiwan, Suttipun and Stanton (2012) in Thailand. Barnard (2000) examined the relationship between the firm"s size and the level of social disclosure.…”
Section: Introductionmentioning
confidence: 57%
“…Como tal, o disclosure socioambiental destina-se a estender a prestação de contas das empresas, indo além do papel tradicional da prestação de contas financeiras aos acionistas. Essa extensão se baseia no pressuposto de que as empresas têm amplas responsabilidades sobre o ambiente em que operam, que ultrapassam a simples responsabilidade financeira (CARDOSO;ALMEIDA, 2016;RIZK;DIXON;WOODHEAD, 2008).…”
Section: Disclosure Socioambientalunclassified